Analisis Laba Bersih Pada Masa Pandemi Covid 19 dari Faktor Modal Kerja dan Penjualan Bersih - Rizka, Inda Noferani; Defitri, Siska Yulia; Wahyuni, Lili (Akuisisi : Jurnal Akuntansi, 2024)
This research aims to prove the effect of working capital and net sales on net profit during the Covid-19 pandemic. The type of research that the author uses is associative quantitative research. Sampling used the purposive sampling method. The population in this study used 14 food and beverage companies listed on the Indonesia Stock Exchange (BEI) in 2018-2021, with a sample size of 56 companies that met the criteria. The analysis method uses the SPSS version 22 for Windows statistical application. The results of this research show that working capital and net sales influence the net profit obtained by food and beverage companies during the Covid-19 pandemic